Factors associated with failure to rescue after liver resection and impact on hospital variation: a nationwide population-based study. Issue 12 (December 2021) - Elfrink, Arthur K.E.; Olthof, Pim B.; Swijnenburg, Rutger-Jan; den Dulk, Marcel; de Boer, Marieke T.; Mieog, J. Sven D.; Hagendoorn, Jeroen; Kazemier, Geert; van den Boezem, Peter B.; Rijken, Arjen M.; Liem, Mike S.L.; Leclercq, Wouter K.G.; et al.
Abstract: Background: Failure to rescue (FTR) is defined as postoperative complications leading to mortality. This nationwide study aimed to assess factors associated with FTR and hospital variation in FTR after liver surgery. Methods: All patients who underwent liver resection between 2014 and 2017 in the Netherlands were included. FTR was defined as in-hospital or 30-day mortality after complications Dindo grade ≥3a. Variables associated with FTR and nationwide hospital variation were assessed using multivariable logistic regression. Results: Of 4961 patients included, 3707 (74.4%) underwent liver resection for colorectal liver metastases, 379 (7.6%) for other metastases, 526 (10.6%) for hepatocellular carcinoma and 349 (7.0%) for biliary cancer. Thirty-day major morbidity was 11.5%. Overall mortality was 2.3%. FTR was 19.1%. Age 65–80 (aOR: 2.86, CI:1.01–12.0, p = 0.049), ASA 3+ (aOR:2.59, CI: 1.66–4.02, p < 0.001), liver cirrhosis (aOR:4.15, CI:1.81–9.22, p < 0.001), biliary cancer (aOR:3.47, CI: 1.73–6.96, p < 0.001), and major resection (aOR:6.46, CI: 3.91–10.9, p < 0.001) were associated with FTR. Postoperative liver failure (aOR: 26.9, CI: 14.6–51.2, p < 0.001), cardiac (aOR: 2.62, CI: 1.27–5.29, p = 0.008) and thromboembolic complications (aOR: 2.49, CI: 1.16–5.22, p = 0.017) were associated with FTR. After case-mix correction, no hospital variation in FTR was observed. Conclusion: FTR is influenced by patient demographics, disease and procedural burden. Prevention of postoperative liver failure, cardiac and thromboembolic complications could decrease FTR.